Impact of Lachancea thermotolerans on chemical composition and sensory profiles of Merlot wines. (1st July 2021) - Hranilovic, Ana; Albertin, Warren; Capone, Dimitra Liacopoulos; Gallo, Adelaide; Grbin, Paul R.; Danner, Lukas; Bastian, Susan E.P.; Masneuf-Pomarede, Isabelle; Coulon, Joana; Bely, Marina; Jiranek, Vladimir
Highlights: Five Lachancea thermotolerans (LT) co-inocula were trialled in Merlot fermentations. Compositional modulations of wines depended on both LT strain and inoculation regime. LT wines had similar or lower pH/ethanol than Saccharomyces cerevisiae (SC) wines. Ethyl lactate was up to thirty-fold higher in some LT wines than in the SC control. Medium chain fatty acids and their ethyl esters were highest in the SC monoculture. Abstract: Wines from warm(ing) climates often contain excessive ethanol but lack acidity. The yeast Lachancea thermotolerans can ameliorate such wines due to partial conversion of sugars to lactic acid during alcoholic fermentation. This study compared the performance of five L. thermotolerans strains in two inoculation modalities (sequential and co-inoculation) to Saccharomyces cerevisiae and un-inoculated treatments in high sugar/low acidity Merlot fermentations. The pH and ethanol levels in mixed-culture dry wines were either comparable, or significantly lower than in controls (decrease of up to 0.5 units and 0.90% v/v, respectively). The analysis of volatile compounds revealed marked differences in major flavour-active yeast metabolites, including up to a thirty-fold increase in ethyl lactate in certain L. thermotolerans modalities. The wines significantly differed in acidity perception, alongside 18 other sensory attributes. Together, these results highlight the potential of some L. thermotolerans strains to produce 'fresher' wines with lower ethanol content and improved flavour/balance.